The Caribbean: ICT tools for women organic farmers ? the Knowing & Growing Network - Tandon, Nidhi (Technical Centre for Agricultural and Rural Cooperation, 2004)
Nidhi Tandon reports on a regional computer training workshop for Caribbean women engaged in organic farming.